Study on risk contagion between rare earth and new energy-related metals markets from the perspective of co-production and co-consumption - Zheng, Renrui; Nong, Hao; Chen, Qishen; Shao, Liuguo; Zhang, Hongtao; Zhang, Yanfei (Frontiers in Physics, 2025)
IntroductionThis paper investigates risk contagion between rare earth and new energy-related metal markets, with a focus on higher-order moment risk spillovers from a co-production and co-consumption perspective. Understanding these dynamics is crucial due to the growing interdependence of these markets and their susceptibility to policy shifts and extreme events.MethodsUsing higher-order moment risk measures, time-domain spillover indexes, and frequency-domain spillover indexes, we analyze return, volatility, skewness, and kurtosis risk spillovers across metal markets from 2014 to 2024. The study employs maximum pairwise spillover portfolio analysis to identify key risk transmission channels.ResultsThe findings reveal that return and volatility risk spillovers increase over time, while skewness risk exhibits short-term high spillovers and kurtosis risk shows long-term persistence, reflecting market sensitivity to asymmetric information and extreme events. Policy changes and major events (e.g., trade disputes, geopolitical tensions) amplify uncertainty and risk contagion. Markets with stable co-production and co-consumption relationships are identified as major risk sources. Frequency-domain analysis highlights the rare earth market’s dominant role in long- and short-term spillovers, with significant external spillover effects.DiscussionThe results underscore the rare earth market's critical influence on new energy metal markets, suggesting that investors should closely monitor its dynamics to optimize risk management. The study provides policymakers and market participants with insights into risk transmission mechanisms and the systemic role of rare earths in the global economy.